Analysis on Flood Control Impact Assessment for Linear Project Involving River and Embankment. Issue 1 (August 2021) - Shi, Junjun; Chen, Qi
Abstract: Aiming at the common problems on flood control impact assessment of linear projects, combined with practical work experience, this paper summarizes and analyzes the characteristics and main impact types of linear projects involving rivers and embankments in recent years, and puts forward the key points of river and embankment impact assessment of linear projects in Zhejiang Province from the aspects of early site selection, construction mode, control factors and remedial measures. It is helpful to improve the quality of flood control impact assessment report, and provide reference for the design, construction, consultation and review of water conservancy department.